Environmental degradation, climate change and health from the perspective of Brazilian Indigenous stakeholders: a qualitative study - Antonio José Grande; Seeromanie Harding; Maria Inês Da Rosa; Ieda M A V Dias; Paulo T C Jardim; Alessandra Aparecida Vieira Machado; Jacks Soratto; Luciane Bisognin Ceretta; Xanthi Zourntos; Regeane Oliveira Suares (BMJ Open)
Background The WHO identifies climate change as the most significant threat to global health systems. Indigenous peoples, whose lives are deeply intertwined with nature, are particularly vulnerable to the impacts of these changes.Objective This study aimed to understand the perspectives of Indigenous stakeholders and public services managers on the interconnectedness of climate change and Indigenous health.Design A qualitative study with 22 Indigenous stakeholders and public service managers on climate change and perceived impact on Indigenous health.Setting and participants Indigenous stakeholders and public service managers on climate change and perceived impact on Indigenous health from Brazil. Data was collected through interviews incorporating two vignette videos depicting environmental and health scenarios. Thematic content analysis was used to analyse the data.Results The analytical process yielded six subcategories that were further grouped into three overarching thematic macro-categories: environmental degradation and climate change in the context of Indigenous peoples; environment, vulnerability and impact on Indigenous mental health; and actions and public health policies for Indigenous peoples.Conclusion The perspectives of Indigenous stakeholders and public service managers on the interconnectedness of climate change and Indigenous health were deeply entrenched in their lived experiences of loss of their lands from deforestation and environmental degradation. They argued strongly for the strengthening of public health policies aimed at the Indigenous peoples, to face many challenges, especially suicide, and to have a voice in decision-making. A sensitive approach that values Indigenous peoples' connections with nature is fundamental to promote their health and well-being.